Patent Protection, Market Uncertainty, and R&D Investment - Andrew A. Toole; Dirk Czarnitzki (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2008)
Real options investment theory predicts current investment falls as uncertainty about market returns increases. In the case of R&D investment, which is usually considered an irreversible form of investment, this effect should be quite pronounced. This paper tests the real options prediction about the R&D investment-uncertainty relationship and further considers how patent protection influences this relationship. Patent protection, by limiting the threat of market rivalry, should mitigate firm-specific uncertainty and stimulate current R&D investment. Our empirical results support both the prediction of real options theory and the mitigating effect of patent protection.
Older version: http://hdl.handle.net/10419/24511
Keywords: O31; O33; C25; 330; Real Options Theory; Uncertainty; R&D; Intellectual Property Protection; Censored Regression